2011
DOI: 10.1039/c0pp90036b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV radiation on aquatic ecosystems and interactions with climate change

Abstract: The health of freshwater and marine ecosystems is critical to life on Earth. The impact of solar UV-B radiation is one potential stress factor that can have a negative impact on the health of certain species within these ecosystems. Although there is a paucity of data and information regarding the effect of UV-B radiation on total ecosystem structure and function, several recent studies have addressed the effects on various species within each trophic level. Climate change, acid deposition, and changes in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
225
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(230 citation statements)
references
References 282 publications
(254 reference statements)
1
225
0
4
Order By: Relevance
“…Under a scenario of global climate change, important changes in the physiology of diverse aquatic organisms are expected (Beardall et al, 2009;Häder et al, 2011), especially due to variations in UVR and temperature levels. In this sense, it has been found that UVR strongly influences photosynthesis and calcification of Emiliania huxleyi under CO 2 -induced ocean acidification (Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Under a scenario of global climate change, important changes in the physiology of diverse aquatic organisms are expected (Beardall et al, 2009;Häder et al, 2011), especially due to variations in UVR and temperature levels. In this sense, it has been found that UVR strongly influences photosynthesis and calcification of Emiliania huxleyi under CO 2 -induced ocean acidification (Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The studied period is 1983-2008, containing (IR). Finally, we work with ultra violet radiation A data (UVA), which comprises from 320 to 400 nm, because the 95% of wavelengths longer than 310 nm reach the surface (Lean et al, 1997) and has a large impact on marine ecosystems (Toole et al 2006;Hefu et al 1997;Slezak et al 2003;Kniventon et al 2003;Häder et al 2011). We use the UVA composite series from the Nimbus7 (1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985), NOAA-9 (1985NOAA-9 ( -1989, NOAA-11 (1989NOAA-11 ( -1992and SUSIM satellites between 1992and 2008(DeLand et al, 2008.…”
Section: Region Of Study and Datamentioning
confidence: 99%
“…In addition, increased amounts of nutrients, originated both from climate change (e.g., atmospheric deposition, wind, precipitation) and from increased land usage (e.g., agricultural and cattle activities) are introduced into estuaries and coastal areas (Findlay, 2005;Monteith et al, 2007). Still, organisms might be exposed to increased levels of solar ultraviolet radiation (280-400 nm) by at least two processes-the depletion of the ozone layer and/or the increased stratification of the water column due to global warming (Beardall et al, 2009;Häder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities have caused major changes on our planet through a process collectively named as climate change (IPCC, 2013), which is responsible for diverse impacts on aquatic organisms and ecosystems (Hays et al, 2005;Häder et al, 2011;Winder and Sommer, 2012). In coastal systems, these changes in climate affect the performance of individuals at various stages of their life history, influence the dispersal and recruitment at the population level and alter the abundance and the strength of interactions and trophic relationships (e.g., predator-prey) at the community level (Harley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%